Coral Reef Potential Based on Diversity at Grand Watudodol Beach, Banyuwangi Regency - Dewi, Agustina Tri Kusuma; Setyaningrum, Ervina Wahyu; Putra, Sandy Maulana (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2025)
Grand Watudodol Beach is a tourist area that offers underwater beauty which is a wealth found in Indonesia. This study aims to determine the water parameters, types of coral reefs and coral reef diversity. The research method used is descriptive method with data collection through direct observation using Line Intercept Transect (LIT) technique. Data analysis method used is diversity index analysis and dominance index analysis. The results of the study found 17 species of coral reefs with the most species found is the type of Montipora danae and the least is the type of Porites lutea. The value of diversity in the waters of Grand Watudodol is included in the moderate category with a value of 2.42. The value of the coral dominance index is included in the medium category, which is in the range of values 0.30 < C < 0.60. The value of oceanographic parameters in the waters of Grand Watudodol is salinity 32 ppt at the location point, the value of temperature parameters at the location point 29-30 °C, pH value obtained 7-8, brightness obtained 7-10 m, current velocity value obtained 0.0678 m/s.